Epidemiological characteristics of ischemic heart disease: A comparative study between China and the world from 1990 to 2021 and prediction to 2036 - Jiale Wu; Jinchan Zhai; Xingyun Zhu; Quan Hao; Jiaqi Yang; Xiaoju Li; Yunhua Hu; Qiang Niu; Yizhong Yan (PLoS ONE, 2025)
Background Ischemic heart disease (IHD) is a major disease that endangers human health. There are relatively few comparative studies on the epidemiological characteristics of IHD. Aims This study aimed to compare and analyze the incidence, prevalence and mortality of IHD in China and the world from 1990 to 2021, predict its change trend from 2022 to 2036, and provide a basis for effective prevention and control of IHD. Methods Data on IHD in China and the world, encompassing age-standardized incidence rate (ASIR), age-standardized prevalence rate (ASPR), and age-standardized mortality rate (ASMR), was extracted from the Global Burden of Disease Study 2021. The Joinpoint regression model was employed to calculate the average annual percentage change (AAPC). The projected data for 2022–2036 were derived through calculations using the Bayesian age-period-cohort model. Results From 1990 to 2021, the growth rates of China’s ASIR, ASPR, and ASMR of IHD were 15.97%, 20.42%, and 17.81% respectively, with annual percentage changes of 0.49%, 0.60%, and 0.49%, all higher than global levels; the annual change rates of incidence, prevalence, and mortality were 3.17%, 3.23%, and 3.54% respectively, also exceeding the world 1.00%, 1.38%, and 0.43%. In 1990, globally and in China, male incidence, prevalence, and mortality of IHD were generally higher than those of females, except that Chinese female mortality was lower; males had higher mortality but lower prevalence and related annual percentage changes, with the disease burden peaking in people aged 80 years and above. Over the next 15 years, the world and Chinese ASMR of IHD is projected to decline, while the male ASIR and ASPR will decrease, and those of females will increase. Conclusions The burden of IHD and the increase rate in China was higher than global figures. Although ASMR for IHD in China and the world will decline over the next 15 years, IHD remains a public health issue that requires ongoing attention.To reduce the burden of IHD, targeted preventive measures and relevant knowledge popularization should be adopted for populations of different genders and ages.